MODERN POSSIBILITIES OF ACHIEVING TARGET BLOOD PRESSURE LEVEL IN HYPERTENSIVE PATIENTS IN OUTPATIENT PRACTICE: THE LEADER STUDY RESULTS - D. V. Nebieridze; A. S. Safaryan; V. A. Vygodin; O. M. Drapkina; S. A. Boytsov (Рациональная фармакотерапия в кардиологии)
Aim. To study the efficacy and safety of the use of hydrochlorothiazide/losartan or amlodipine/losartan fixed combinations in patients with arterial hypertension (HT) in real clinical practice.Material and methods. A total of 13,863 adult patients with HT were enrolled into the observational study. One month ago, according to the indications, they were prescribed therapy with amlodipine/losartan (5/50, 10/50, 5/100, 10/100 mg) or hydrochlorothiazide/losartan (12.5/50, 12.5/100, 25/100 mg). The study included only those patients who did not reach the target blood pressure (BP) level in previous therapy, or were not treated earlier. The study duration was 3 months.Results. 79.17% of patients reached the target BP level by the end of the study after 3 months. High efficacy of HT treatment persisted in concomitant diseases. The target BP level was achieved in 76.42% of patients with coronary heart disease, 73.98% of patients with diabetes and 78.34% of patients with chronic obstructive pulmonary disease. According to the results of the questionnaire on a 7-point scale, 93% of doctors gave the maximum score on the treatment effectiveness and 97% – on the treatment safety. During the entire treatment period, no one patient discontinued participation in the study due to adverse events. Conclusion. The study demonstrated high efficacy and safety of HT patients treatment with hydrochlorothiazide/losartan and amlodipine/losartan fixed combinations in real clinical practice. The majority of patients who were previously treated ineffectively or did not receive treatment achieved adequate BP control during treatment with hydrochlorothiazide/losartan or amlodipine/losartan fixed combinations.